Expanding the toolkit for industry analysis: an application of the value capture concept - Osen, Marte Risdal (2017)
The purpose of this study is to apply value-based business concepts to a product in order to gain insight into the competitive environment within its related industry. This case study is based upon qualitative information from the decision makers in a company producing a product. It is shown that the value based business theories, when organised into one framework, does facilitate the organisation of data, and hence some conclusions about the competitive dynamics of the industry can be drawn. The approach to thinking about business suggested by the value based business concepts might hence lead to insights that can serve as a new background for strategic decisions.